2016
DOI: 10.1186/s12014-016-9126-9
|View full text |Cite
|
Sign up to set email alerts
|

Plasma degradome affected by variable storage of human blood

Abstract: BackgroundThe successful application of—omics technologies in the discovery of novel biomarkers and targets of therapeutic interventions is facilitated by large collections of well curated clinical samples stored in bio banks. Mining the plasma proteome holds promise to improve our understanding of disease mechanisms and may represent a source of biomarkers. However, a major confounding factor for defining disease-specific proteomic signatures in plasma is the variation in handling and processing of clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 38 publications
2
39
0
Order By: Relevance
“…We measured the amounts of 15 plasma proteins at a single LC‐MRM‐MS run to investigate the pre‐analytical effects of storage time and temperature on blood samples. The proteins were chosen from a dataset of PROTOPMAP analysis with one exception . Seven proteins were chosen from the top 20 presumed to be strongly associated with pre‐analytical effects.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We measured the amounts of 15 plasma proteins at a single LC‐MRM‐MS run to investigate the pre‐analytical effects of storage time and temperature on blood samples. The proteins were chosen from a dataset of PROTOPMAP analysis with one exception . Seven proteins were chosen from the top 20 presumed to be strongly associated with pre‐analytical effects.…”
Section: Resultsmentioning
confidence: 99%
“…In this method, analytes are quantified by using a known amount of corresponding stable isotope‐labeled proteins. A cytosolic protein, PFN1, was reported to increase in the plasma prepared from blood stored for a long time . This implies that PFN1 leaked from the blood cells into the soluble fraction during blood storage before plasma isolation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the identified biomarker candidates, the proteolytic processing of the transcriptional regulator STAT1 was found to be highly upregulated in HCC tissue, indicating its pathological relevance and diagnostic potential. Interestingly, PROTOMAP was also used to evaluate the effect of storage temperature on the stability of clinical blood samples . The results showed that blood storage at room temperature caused the degradation of about 4% out of 820 identified plasma proteins, which could cause potential bias in identifying and assigning potential markers.…”
Section: Discovery Of Protease Substratesmentioning
confidence: 99%